2022
DOI: 10.3390/molecules27010259
|View full text |Cite
|
Sign up to set email alerts
|

The Wound-Healing Effect of Mango Peel Extract on Incision Wounds in a Murine Model

Abstract: Mangifera indica can generate up to 60% of polluting by-products, including peels. However, it has been shown that flavonoids and mangiferin are mainly responsible for the antioxidant, anti-inflammatory, and antibacterial activities closely related to the wound-healing process. The chemical composition of MEMI (methanolic extract of M. indica) was analyzed by HPLC-DAD, as well as concentrations of total phenol (TPC) and flavonoids (TFC) and antioxidant activity (SA50). Wound-healing efficacy was determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
3
14
0
1
Order By: Relevance
“…Espinosa-Espinosa et al [ 58 ] researched the effect of methanol extract of M. indica peel on incision wounds in a murine model using 5% dexpanthenol as positive control. According to the researchers, the incision model was used to assess the healing efficiency of the plant extract.…”
Section: Mechanism Of Action Of Mango Phytochemicalsmentioning
confidence: 99%
“…Espinosa-Espinosa et al [ 58 ] researched the effect of methanol extract of M. indica peel on incision wounds in a murine model using 5% dexpanthenol as positive control. According to the researchers, the incision model was used to assess the healing efficiency of the plant extract.…”
Section: Mechanism Of Action Of Mango Phytochemicalsmentioning
confidence: 99%
“…Other research studies similarly indicated that the MSK extract exhibited antibacterial properties against S. aureus and P. aeruginosa [ 3 , 5 , 7 , 8 ]. Apart from the antibacterial properties of MSK extracts, Espinosa-Espinosa et al developed MSK ointment from Ataulfo kernel, and the result showed antibacterial activity against S. aureus and P. aeruginosa [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracts rich in phenolic compounds from Diospyros mespiliformis , Haplophyllum tuberculatum, and Mangifera indica showed important antioxidant, anti-inflammatory, and antimicrobial activities when evaluated in different models of wound healing [ 106 , 107 , 108 ]. Rocha et al [ 109 ] evaluated the antioxidant, anti-inflammatory, and healing activities of Artemisia campestris L. hydrodistillation residual water and its essential oil, finding that the residual hydrodistillation water showed promising antioxidant and anti-inflammatory activities without causing toxicity in the macrophages and fibroblasts.…”
Section: Mechanisms Of Action Of the Natural Products In Wound Healingmentioning
confidence: 99%